Karl Marx on religion: the perspective of Boko Haram in Nigeria - Igboin, Benson Ohihon (Journal of religious culture, 2014)
One memorable quote from Karl Marx’s conception of religion is, “religion is the opium of the masses.” By this, he critiqued religion as an analgesic that dulls the senses, thus inducing a false sense of satisfaction, and preventing the oppressed from revolting against the grubby socio-economic system. As the sigh of the oppressed, religion makes them to resign to fate since it only gives an unrealistic eschatological hope. Rather than conceive religion from this prismatic way, contemporary events have shown that religion has become an amphetamine or a catalyst for revolt, not only at the global but also national level. This work argues that religion is used as an amphetamine, an energizing pill, to pursue other goals than religious as depicted in the activities of Boko Haram sect, which has raised security challenges in contemporary Nigeria.